Lo sviluppo di servizi di trasporto innovativi a supporto della mobilità dei crocieristici: una valutazione di fattibilità strategica per il porto di Ragusa (Dubrovnik) - Marco Mazzarino; Silvia Battino (Bollettino della Società Geografica Italiana)
Following the increase of cruise traffic, the area of Ragusa (Dubrovnik) suffers from the negative impacts on the urban transport system, especially in terms of congestion and pollution, along the main connections from the main cruise terminal (Gruž) to the Old Town. The aim of the paper consists of carrying out an original feasibility study – fostered by local stakeholders and policy-makers – based on a sound empirical methodology and data collection so as to put forward an innovative local maritime transport service complementary to traditional urban transport solutions, which mainly consist of pedestrian routes and land-based public transport services. Following a comprehensive literature review and a best practice analysis, the paper builds upon a number of original scenarios comparing the current situation with a number of transport alternatives (a local maritime service and a pedestrian tunnel) to be used by cruise tourists accessing the historical center so as to support local policy-makers. Results show the feasibility of the local maritime option, which determines a significant reduction in urban congestion and pollution.